6(x+1)+3=2x+17

Simple and best practice solution for 6(x+1)+3=2x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+1)+3=2x+17 equation:



6(x+1)+3=2x+17
We move all terms to the left:
6(x+1)+3-(2x+17)=0
We multiply parentheses
6x-(2x+17)+6+3=0
We get rid of parentheses
6x-2x-17+6+3=0
We add all the numbers together, and all the variables
4x-8=0
We move all terms containing x to the left, all other terms to the right
4x=8
x=8/4
x=2

See similar equations:

| -x/6-(-31)=64 | | 5x-1=x+10 | | 5x+3-2x=18-4x | | 72x^2+2x-35=0 | | 100=21.8+a | | 5(m+1)=7(m-1 | | 6x-1=-6x+11 | | 4x+1+2x+3=10x-20 | | 3/4x+2-5/4x=-6 | | 33=15w=3w-w+4w | | 4y^2+13y-12=0 | | 5x9=-3x-12+5x | | 39y+7y^2=18 | | 4/16x-261=1/x^2 | | 10/x=5/2x+45 | | -18u-18=-2u-12 | | 4(-4+x)=5x+1/4 | | 3x+5+5x-18=90 | | m-6=-11+2m | | 8b+28=-4+4b+12 | | √-8+6x=x | | (2/3)z=41/4 | | -7=2x=-45x | | 6=((2/3)x) | | 7n+12=(-23) | | g=19-21 | | √8-6x=x | | 243=27t | | 16n+-16=4n+2 | | 4=6+f | | 0=((2/3)x)-6 | | -7=2x+-4=5x |

Equations solver categories